Analisis Faktor-Faktor dan Persepsi dalam Menggunakan Mobile Banking terhadap Minat Nasabah - Oktavyana; Handra Tipa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test whether security factors, trust, perceived ease of use and perceived usefulness influence customer interest when using mbanking. This research uses a quantitative approach by distributing questionnaires using Likert scale measurements. The population in this study were students from Batam International University, Batam University, Batam Polytechnic University, and Universal University. The sample in this study used simple random sampling and the sample was determined using the Slovin formula, totaling 100 respondents. Partial research results show that Perceived ease of use has a significant effect on Customer Interest, Perception of Usefulness has no significant effect on Customer Interest, Security has no significant effect on Customer Interest, and Trust has a significant effect on Customer Interest. Simultaneously, perceived convenience, perceived usefulness, security and trust have a significant effect on customer interest.